Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/srep17272
|View full text |Cite
|
Sign up to set email alerts
|

The distribution and characteristics of LDL receptor mutations in China: A systematic review

Abstract: Familial hypercholesterolemia (FH) is a common and serious dominant genetic disease, and its main pathogenic gene is the low-density lipoprotein receptor (LDLR) gene. This study aimed to perform a systematic review of LDLR mutations in China. Using PubMed, Embase, Wanfang (Chinese), the Chinese National Knowledge Infrastructure (Chinese), and the Chinese Biological and Medical database (Chinese), public data were limited to December 2014. The Medical Subject Headings terms and the following key words were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 39 publications
4
33
1
Order By: Relevance
“…Likewise, mutations in the APOB gene were seen in 6% of our patients with FH with three double heterozygous patients harboring both APOB and LDLR mutations. In contrast to Caucasian populations, NM_000384.2( APOB ): c.10579 C>T was the most frequent APOB mutation in our study, and this variant was also the main APOB gene mutation among FH subjects in Taiwan and in China (Chiou & Charng, ; Jiang et al., ). We have sequenced all the coding regions of the PCSK9 gene and did not find any gain‐of‐function mutations in our cohort.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…Likewise, mutations in the APOB gene were seen in 6% of our patients with FH with three double heterozygous patients harboring both APOB and LDLR mutations. In contrast to Caucasian populations, NM_000384.2( APOB ): c.10579 C>T was the most frequent APOB mutation in our study, and this variant was also the main APOB gene mutation among FH subjects in Taiwan and in China (Chiou & Charng, ; Jiang et al., ). We have sequenced all the coding regions of the PCSK9 gene and did not find any gain‐of‐function mutations in our cohort.…”
Section: Discussioncontrasting
confidence: 66%
“…Majority of the Chinese population in Hong Kong originated from southern China, and the three most common mutations in the LDLR gene were the NM_000527.4(LDLR): c.1241 T>G (10%), NM_000527.4(LDLR): c.1474G>A (6%), and NM_000527.4(LDLR): c. 682G>A (4%). The distribution of the common mutations in Hong Kong seems to differ from those reported in China and Taiwan (Chiou & Charng, 2012;Jiang et al, 2015). The common mutations reported in Chinese populations from the North of China (NM_000527.4(LDLR): c.1879G>A and NM_000527.4(LDLR): c.313+1G>A) and from Taiwan (NM_000527.4(LDLR): c.986G>A and NM_000527.4(LDLR): c.1747 C>T) were also present in our population but at a lower frequency.…”
Section: Discussionmentioning
confidence: 79%
“…Arterial cells (macrophages, pericytes, and smooth muscle cells) take up these particles in an unregulated manner bypassing the specialized LDL receptor [3][4][5]. The mechanism of interaction of native (unmodified) LDL with a specific cell receptor is currently well known [5][6][7][8]. This interaction does not lead to excessive deposition of intracellular lipids since the lipid components of LDL are utilized by cells, and the excess is removed.…”
Section: Introductionmentioning
confidence: 99%
“…In China, there are few studies analyzing FH patients using genetic analysis, and novel genetic variants identified remain scarce . The rate of timely diagnosis and treatment of FH is far from satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…8 In China, there are few studies analyzing FH patients using genetic analysis, and novel genetic variants identified remain scarce. 9 The rate of timely diagnosis and treatment of FH is far from satisfaction. As PMI represents a critical clinical manifestation of patients with FH, the aim of this study was to investigate the prevalence of FH using genetic testing in a cohort of Chinese patients with PMI, and to evaluate different diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%